Fear of Covid-19 and Covid-19 stress and association with sociodemographic and psychological process factors in cases under surveillance in a frontline worker population in Borneo - Tze, Nicholas Ping Pang; Gracyvinea Nold Imon; Elisa Johoniki; Mohd Amiruddin Mohd Kassim; Azizan Omar; Syed Sharizman Syed Abdul Rahim; Firdaus Hayati; Mohammad Saffree Jeffree; Jun, Rong Ng (MDPI, 2021)
COVID-19 stress and fear of COVID-19 is an increasingly researched construct in the general population. However, its prevalence and association with sociodemographic factors and psychological process variables has not been explored in frontline workers under surveillance in a Bornean population. This study was a cross-sectional study using a sociodemographic questionnaire incorporating two specific epidemiological risk variables, namely specific questions about COVID19 surveillance status (persons under investigation (PUI), persons under surveillance (PUS), and positive cases) and the nature of frontline worker status. Furthermore, five other instruments were used, with three measuring psychopathology (namely depression, anxiety and stress, fear of COVID19, and stress due to COVID-19) and two psychological process variables (namely psychological flexibility and mindfulness). Kruskal–Wallis and Mann–Whitney tests were performed to assess if there were significant differences in psychopathology and psychological process variables between sociodemographic and epidemiological risk variables. Hierarchical multiple regression was further performed, with depression, anxiety, and stress as dependent variables. There were significant differences in the fear of COVID-19 between positive cases, PUI, and PUS. The fear of COVID-19 scores were higher in positive cases compared to in PUS and PUI groups. Upon hierarchical multiple regression, mindfulness and psychological flexibility were significant predictors of depression, anxiety, and stress after controlling for sociodemographic and epidemiological risk factors. This study demonstrates that exposure to COVID-19 as persons under investigation or surveillance significantly increases the fear of COVID-19, and brief psychological interventions that can positively influence mindfulness and psychological flexibility should be prioritized for these at-risk groups to prevent undue psychological morbidity in the long run.